Body Dissatisfaction and Its Association with Health-Related Factors in Rural and Urban Mexican Adolescents from the State of Jalisco - María Rivera-Ochoa (MDPI AG, 2021)
Background: To better understand Mexican adolescent’s body self-perception, this study aimed to analyze their body dissatisfaction (BD) levels according to sex and place of residence. We also aimed to explore differences in body composition (BC), physical fitness (PF), and physical activity (PA) between satisfied and dissatisfied adolescents and to find the associations between BD and these parameters. Methods: Cross-sectional, observational study carried out in Jalisco (Mexico) in which 451 adolescents (43.68% males, 43.90% rural) aged 13–17 years were evaluated. BD and self-perceived PF and PA were assessed with validated questionnaires, while objectively measured PF (strength, explosive strength, speed-agility, and cardiovascular fitness) was assessed using field tests. To evaluate BC, anthropometric measures and bioelectric impedance analysis were carried out. Regression analysis was used to ascertain the associations between health-related factors and body dissatisfaction. Results: Girls obtained higher scores on the BD questionnaire than boys (11.12 ± 3.13 vs. 10.33 ± 2.73; p < 0.05), whereas no geographical differences between rural and urban adolescents were found. BD was positively associated with higher fat mass (β = 0.15; p < 0.001), and negatively associated with muscle mass and PF (β = −0.24 and β = −0.23; p < 0.001). However, PA was not associated with any of the measured parameters. Conclusions: selected parameters of BC, PF, and sex have an impact on the Mexican adolescent’s body satisfaction levels and should be considered when designing future health policies.